Loss Attention in a Dual-Task Setting. (February 2014) - Yechiam, Eldad; Hochman, Guy
The positive effect of losses on performance has been explained as stemming from the increased weighting of losses relative to gains. We examine an alternative possibility whereby this effect is mediated by attentional processes. Using the dual-task paradigm, we expected that positive effects of losses on performance would emerge under attentional scarcity and diffuse to a concurrently presented task. In Study 1, decision performance was compared for a task that involved either gains or losses and was performed either alone or as a secondary task. The results showed a significant 40% improvement in performance in the loss condition, but only under conditions of resource scarcity, when the task was a secondary one. In Study 2, the same task was presented as a primary task. Again, losses were associated with improved performance in the secondary task. Given that this secondary task did not include losses, these findings demonstrate an attentional spillover effect.